2008
DOI: 10.1002/smll.200701236
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Nanofibers Induced by High‐Energy Ion Irradiation of Bulk GaSb

Abstract: Embedded GaSb nanofibers with an intact surface layer are formed by high‐energy ion irradiation of bulk single‐crystal GaSb (see image). Distinct regimes are present within the fiber layer and the effects of varying implant parameters on the fiber regimes are reported. A growth model for nanofibers is presented, as well as a model for the dose‐dependant removal of the surface cover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…The fundamental mechanism for fabrication of porous Si centers around chemical etching [3,4], and while some studies have shown that ion irradiation prior to chemical etching can be used to control certain properties of porous Si [5,6], all porous Si fabrication processes use some combination of anodization or stain etching to produce the porosity in Si. In contrast, dense porous networks have been fabricated in many semiconductor materials, including Ge [7][8][9], GaSb [10][11][12], and InSb [13][14][15], purely by high-energy ion irradiation of the target material. These porous structures consist of interconnected networks of voids ranging in size from tens to hundreds of nanometers in diameter, and void growth and coalescence results in confinement of the matrix material into fibers or cell walls tens of nanometers in thickness.…”
Section: Introductionmentioning
confidence: 94%
“…The fundamental mechanism for fabrication of porous Si centers around chemical etching [3,4], and while some studies have shown that ion irradiation prior to chemical etching can be used to control certain properties of porous Si [5,6], all porous Si fabrication processes use some combination of anodization or stain etching to produce the porosity in Si. In contrast, dense porous networks have been fabricated in many semiconductor materials, including Ge [7][8][9], GaSb [10][11][12], and InSb [13][14][15], purely by high-energy ion irradiation of the target material. These porous structures consist of interconnected networks of voids ranging in size from tens to hundreds of nanometers in diameter, and void growth and coalescence results in confinement of the matrix material into fibers or cell walls tens of nanometers in thickness.…”
Section: Introductionmentioning
confidence: 94%
“…By considering the previous evidences reported for GaSb, 27 He implanted Si ͑Ref. 21͒ and the results presented in this paper for TiO 2 , we propose the mechanism schematized in Fig.…”
Section: Surface Nanostructuring Of Irradiated Tiomentioning
confidence: 99%
“…Interestingly, for both materials similar structures consisting of voids, cellular structures or nanorod surface patterns have been observed. For GaSb irradiated with 30 keV Ga + ions, Perez-Bergquist et al 27 found that for low doses ͑1.3ϫ 10 15 ions/ cm 2 ͒ the first layers of the material breached, exposing a thin porous regions to the surface. By contrast, at higher doses ͑6.5ϫ 10 15 ions/ cm 2 ͒, the pores grew outwards developing a typical nanorod surface pattern.…”
Section: Surface Nanostructuring Of Irradiated Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of GaN, [5][6][7][8] nitrogen bubbles and gallium nanocrystals are formed in the amorphized layer by ion irradiation. In the case of GaSb [9][10][11][12][13][14][15][16][17] and InSb, 9,17,18) unusual behaviors, such as elevation, swelling, and the formation of holes, voids, nanofibers, and cellular structures with nano to submicron dimensions, are observed on irradiated surfaces. Similar phenomena occur in irradiated Ge surfaces (for example, see Refs.…”
Section: Introductionmentioning
confidence: 99%